Trends in suicide mortality among people with HIV after diagnosis during 2012–18: a retrospective, national cohort study in China. Issue 2 (February 2022) - Chen, Fangfang; Cai, Chang; Wang, Shengfeng; Qin, Qianqian; Jin, Yichen; Li, Dongmin; Ge, Lin; Li, Peilong; Cui, Yan; Tang, Houlin; Lv, Fan
Summary: Background: Little is known about suicide mortality among people with HIV in low-income and middle-income countries. This study aimed to assess suicide mortality and its temporal change among people with HIV after diagnosis, then describe potential risk factors. Methods: This nationwide, population-based cohort study used data from the China Information System for Disease Control and Prevention (CISDCP), which continually enrolled people diagnosed with HIV in mainland China. We included all people with HIV diagnosed between Jan 1, 2012, and Dec 31, 2018, who were aged 15 years or older at diagnosis. Follow-up started from the date of HIV diagnosis to the date of death, date of last follow-up visit, or Dec 31, 2018, whichever came first. Crude suicide mortality was calculated as the number of suicide deaths divided by person-years at risk in 2012–18 and compared by time after HIV diagnosis. Standardised mortality ratios (SMRs) were used to compare the relative risk of suicide deaths in people with HIV with the general population. We compared the trends of suicide mortality across three diagnosis year groups (2012–13, 2014–15, and 2016–18) using cumulative incidence curve of suicide. Competing-risk models were used to explore the potential risk factors of suicide. Findings: 770 656 people diagnosed with HIV were included in the CISDCP database, 763 287 of whom were aged 15 years or older at diagnosis and had follow-up information available. During follow-up, 2825 (2·0%) of 144 729 all-cause deaths were due to suicide, with a mortality of 142·8 deaths by suicide per 100 000 person-years (95% CI 137·7–148·2). People with HIV were at an increased risk of suicide compared with the general population (SMR 20·9 [95% CI 20·2–21·7]). The greatest risk was during the first 3 months after diagnosis (SMR 98·1 [93·1–103·4]), which then decreased but was still elevated after the first year (SMR 9·2 [8·5–9·8]). Late diagnosis and never on antiretroviral therapy were independent risk factors for suicide. Interpretation: Suicide mortality decreased during the study period, which coincided with improvement in access to care and treatment coverage. This study suggests the importance of targeted suicide prevention for people with HIV throughout the course of diagnosis and that the focus of efforts should be concentrated on the first 3 months after diagnosis. Our findings highlight the urgent need to integrate suicide screening and prevention in HIV care. Funding: Young Scholar Scientific Research Foundation of National Center for AIDS/STD Control and Prevention, Chinese Center for Disease Control and Prevention. Translation: For the Chinese translation of the abstract see Supplementary Materials section.